Festina Lente as a Behaviorally Oriented Self-Regulation Pattern Aligned with Metacognitive Principles in Higher Education - Balogh, Attila; Iľko, Ivan (Journal of Social and Scientific Education, 2026)
Modern higher education increasingly emphasizes efficiency and rapid knowledge acquisition, often at the expense of reflection and depth of understanding. This study explores the ancient principle festina lente (“make haste slowly”) as a pattern of learning-related behaviors aligned with principles of metacognitive self-regulation among university students. Participants completed a modified version of the Motivated Strategies for Learning Questionnaire (MSLQ) twice, reflecting their learning-related perceptions at the beginning and end of the semester. The instrument captured two dimensions of festina lente–related behaviors: (a) Academic Preparation (AP) and (b) Non-required Enrichment (NE). The results indicated statistically significant temporal increases in both AP and NE scores (p < 0.05), although effect sizes were small. Female students reported higher engagement in AP-related behaviors compared to male students, while no gender differences were observed in the NE dimension. These findings document exposure-based temporal patterns in learning behaviors conceptually aligned with metacognitive principles rather than evidence of strategy acquisition or metacognitive development. The study highlights the relevance of deliberate pacing and sustained engagement in higher education and suggests directions for future research combining behavioral indicators with direct measures of metacognitive regulation in larger and more diverse samples.